Identifikasi Stuktur Internal Organ Reproduksi pada Tumbuhan Angiospremae dan Gymnospermae - Hanum Salsabila; Husna Aulia Muthi’ah; Mochammad Ikbal Fatoni; Muhammad Abdan Syahida Arifin; Nabila Nur’arifah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Reproduction in plants from generative sex can occur with fertilization (amphimixis), or without fertilization (apomixis). Data were obtained through experimental experiments by observing under a microscope by observing the anatomical structure of the anthers and the structure of the flower ovary. Passiflora vitifolia is a species with bright red flowers that are between ten and fifteen centimeters in diameter when fully bloomed, the reproductive organs consist of stamens, pollen, pistils and ovaries. Gymnosperms are a group of open-seeded plants that do not have true flowers, and their reproductive organs consist of distinct male and female strobilus. This differentiates them from flowering plants (angiosperms). Male strobilus have microsporophylls which produce pollen, while female strobilus have macrosporophylls which function as a place for seed development.